Analysis of the Application of Environmental Cost Accounting at Pt. Nusantara Plantations - Islamin, Fahdilatul; Yasa, I Putu Buda; Azim, Muhammad (Business Management, 2025)
The aim of this research is to find out and analyze how companies identify, recognize, measure, present and disclose environmental costs in financial reports. The research was conducted at PT. Perkebunan Nusantara V Sei Rokan. This research uses primary (qualitative) data by means of interviews and secondary (quantitative) data from company financial reports. The results show that companies in recognizing waste processing operational costs (environmental costs) are included as a component of production costs with the consideration that waste arises as a result of the production process. Disclosure of environmental issues in financial reports has not yet been specifically regulated in the applicable accounting standards, so that its implementation is in accordance with the policies of each company.